1999
DOI: 10.1902/jop.1999.70.2.189
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cyclosporin A on Alveolar Bone: An Experimental Study in the Rat

Abstract: KyushuDental Society AdtiScaftbl 45 (4) :425-445, 1991. fi SSE Vc St # 6 !llva7EEi・ttimaes o ,Eif ng fi Ek ei ma-g-6 =,ge asM1fi-t < eitwtwNaR(k-pt n 1>-JLNiltsptJk7,JNvadvgiiP\suU (lee : ]k")iZ\ijR) SPnt 3 lf 6 fi 25 eXff Combined Debility Kimura) Three-week-old male rats of Wi$tar strain were given calcium-deficient food for 3 weeks and experimental bone debility was induced in them. Food was then changed to normal standard food and the effect on the debilitated alveolar bones of the treatment combined with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
1
6

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 42 publications
5
25
1
6
Order By: Relevance
“…Some studies have linked the adverse effects of osteoporosis and osteopenia to use of CsA. 4,5,21,30,31 These features regarding alveolar bone metabolism would be associated with increased osteoclastic activity and reduction of bone formation in the presence of CsA. In this study, the authors suggested that CsA immunosupression might have caused a decrease in periodontal breakdown.…”
Section: Discussionmentioning
confidence: 78%
“…Some studies have linked the adverse effects of osteoporosis and osteopenia to use of CsA. 4,5,21,30,31 These features regarding alveolar bone metabolism would be associated with increased osteoclastic activity and reduction of bone formation in the presence of CsA. In this study, the authors suggested that CsA immunosupression might have caused a decrease in periodontal breakdown.…”
Section: Discussionmentioning
confidence: 78%
“…Phamacodynamically, CyA is considered to inhibit the actions of IL-2, which is thought to trigger psoriatic lesions (Borel et al 1976;Mueller and Herrmann 1971;Finzi et al 1989;Ho et al 1990;Borel 1990;Abe et al 1997). However, CyA has also been reported to inhibit the DNA synthesis of keratinocytes and their subsequent proliferation (Fu et al 1999;Fornoni et al 2001). Therefore, CyA might bring about an improvement not only by immune suppression, but also by suppressive effects on keratinocyte proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, CyA has been reported to modify the synthesis and degradation of extracellular matrix (ECM) by osteoblasts and gingival fibroblasts (Boltchi et al 1999;Fu et al 1999;Fornoni et al 2001;Bostorm et al 2005;Bullon et al 2007). The histopathological changes in affected skin before and after CyA administration without topical-treatment or phototherapy are obvious in psoriasis vulgaris.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that CsA can decrease osteoclast formation and consequently bone resorption by inhibiting the fusion of pre‐osteoclasts in vitro (Orcel, Denne, & de Vernejoul, ). On the other hand, an in vivo study in rats has demonstrated induced osteopenia characterized by increased osteoclasia in periodontal sites and reduced bone formation (Fu, Hsieh, Nieh, Wikesjo, & Liu, ). A recent study (Espitalier et al, ) has showed effective bone repair and a significant increase in bone regeneration when CsA was daily administered in a rat model of bone marrow allograft.…”
Section: Discussionmentioning
confidence: 99%